Art in Health: Malaysian Experience - Muhammad Asyraf Mohd Bakri; Mohammad Kamal Sabran (Wacana Seni Journal of Arts Discourse, 2022)
Art in healthcare has gone through a broad movement around the world, encompassing how art influences patient care, the hospital environment, care, and community development in medical and other contexts. Therefore, in Malaysia, whether there is a development of art in health has been explored, and this study would like to know the extent to which the development of art intervention in health occurs. Qualitative data through the interview method was used in this study by interviewing medical doctors who had been involved in art interventions in health. Having artistic knowledge in health research is very important to know and understand that many approaches have been used to date.